ANALISIS TERBATASNYA PANDANGAN AREA PEMANDUAN PERSONIL ACO TERHADAP PEMBERIAN PELAYANAN AFIS DI PERUM LPPNPI MUARA BUNGO - Oktavio Nugraha Dwi Putra; Sudrajat; Sumpono Bayu Aji (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
UPNP Muara Bungo which has the status as a Business Entity within the State-Owned Enterprises provides Aerodrome Flight Information services. Activities organized by UPNP Muara Bungo are Air Traffic Services, Aeronautical Telecommunication Services, Aeronautical Information Services, Aeronautical Meteorological Services, and Search and Rescue. The problem studied in this final project is how the limited view of the pilotage area of ​​Aeronautical Communication Officer personnel affects the provision of Aerodrome Flight Information Service services. In this writing, the author is guided by Annex 11, ICAO 211, PP No. 77 of 2012, PER.028/LPPNPI/X/2017, RI Law No. 1 of 2009, CASR 170, SKEP/347/XII/1999, and PM 65 2017. The research method that the author uses is using observation, interviews with Perum LPPNPI Muara Bungo personnel and Perum LPPNPI Jambi Branch, documentation, questionnaires, and literature studies. The data analysis method used is descriptive quantitative method and measurement using a Likert scale. This study obtained a Correlation Coefficient score of 0.2, which means that the results obtained do not produce a minus score, meaning that the relationship is positive, i.e. if the X variable increases, the Y variable also increases. So it can be concluded that there is a limited influence of the view of the area of ​​​​the pilotage of Aeronautical Communication Officer personnel on the provision of Aerodrome Flight Information Service services at Perum LPPNPI Muara Bungo.